Book Review: Christ and Culture: Revisited - L. Paembongan, Raka Saden Priya (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
The discussion about Christ and Culture is endless and will cause tension as time progresses. Carson in this book looks again from a biblical-theological perspective on the relationship between Christ and Culture, that the relationship between Christ and Culture cannot be separated from the absolute source of truth, namely the Bible. The series of events from creation, the fall, the incarnation, the death and resurrection of Jesus, to the Last Days are important to find a way between Christ and culture in this age.